The Rolling Stock Recovery Problem - Groth, Julie Jespersen; Larsen, Jesper; Clausen, Jens (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
DSB S-tog (S-tog) operates on the double tracked, suburban network surrounding Copenhagen, Denmark. S-tog is the sole operator on the network. The network is owned and controlled by the infrastructure manager BaneDanmark. During the last years there has been an increased focus on developing tools to aid the planning process in railway transportation. The tools are computer software, which can fully or partly automate some part of the planning process. As in other industries the initial focus has been on strategic, tactical and operational planning. Only lately focus has turned to the area of short term and real time planning. This paper concentrates on the area of rolling stock real time planning. In practice rolling stock dispatchers monitor the operation of the rolling stock plan and the depot plans. When the rolling stock plan is disrupted, the rolling stock dispatcher makes real time decisions on the re-assignments of train units to train tasks. This process is called recovery. An automated tool will improve the recovery process, help supplying sufficient seat capacity for passengers and reduce the operating cost.